On-Demand Oral Pre-exposure Prophylaxis with Tenofovir/Emtricitabine: What Every Clinician Needs to Know - Saberi, Parya (J Gen Intern Med, 2020)
Based on the results of the IPERGAY study, on-demand HIV pre-exposure prophylaxis (PrEP; also known as “non-daily PrEP,” “event-driven PrEP,” or “2-1-1 PrEP”) is being requested more frequently by patients who have intermittent sexual risk or are unable/unwilling to take daily PrEP; therefore, clinicians will be increasingly required to familiarize themselves with its appropriate use. In this perspective, we summarize data related to on-demand PrEP, describe advantages and disadvantages for this alternative dosing strategy, and provide clinical counseling points.